Nutrition and Women Bone Health (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Nutrition is a key element that has the potential to reduce bone loss and fracture risk. While nutrition has become one of many variables that can impact bone health, there is a need to formulate and maintain nutritional approaches and techniques for the prevention and treatment of bone health-associated disorders that may affect women's health. This book, compiling articles published during 2021–2022, belongs to the Topical Collection " Nutrition and Women Bone Health". The application of the knowledge presented here may subsequently provide further support for preventive approaches based on population-based interventions. Key major topics related to the relationship between different nutrients and women's bone health are discussed using high-quality research methodologies, including randomized clinical trials and observational studies, all of which are led by notable nutritional and clinical researchers. The Guest Editor intends for this book to contribute to expanding the body of knowledge on bone health and nutrition in women as well as highlight the pivotal role that this interaction plays in human health throughout populations. The findings represent a beginning point for future research, which should progressively be focused on experimental investigations with diverse populations and demographic groups in order to further understand the link between nutrition and bone health in women.